A higher taxonomic richness does not ensure the functional resilience of saproxylic beetle communities in evergreen Quercus forests. (19th July 2021) - Pérez‐Sánchez, Diana; Mason, Norman W. H.; Brustel, Hervé; Galante, Eduardo; Micó, Estefanía
Abstract : 1. Despite the fact that insects are suffering a global decline, little is known about the extent to which species loss affects functional diversity. Thus, to understand the relationship between taxonomic and functional diversity metrics, we focused on saproxylic beetles, which perform vital functions in forest ecosystems. 2. Beetles were collected monthly for a year using flight interception traps placed in three protected areas of mature evergreen Mediterranean Quercus forests. Five morphological traits, one phenological trait, and one physiological surrogate trait were measured, and trophic guild identities were determined. Two taxonomic and six functional metrics were assessed to determine their relationships. 3. Taxonomic and functional diversity patterns, as well as trait patterns, differed depending on the protected areas, as they were influenced by habitat and microhabitat characteristics. Generally, a high number of species tended to support high values of functional richness, but did not ensure high values of functional redundancy, thus affecting the resilience of communities. 4. A 5% of species loss strongly affected the functional redundancy of communities, making them more vulnerable. Functional richness, however, was not affected, since it was associated with a high number of redundant species. Thus, the way species loss affected communities is highly dependent on the presence of rare or redundant species. 5. Taxonomic and functional diversity metrics should be used as complementary tools for conservation purposes. In this way, the comparative analysis of taxonomic and functional patterns may help to predict the vulnerability of saproxylic assemblages to changes or disturbances. Abstract : Despite the functional importance of saproxylic beetles, little is known about the extent to which species loss affects functional diversity, particularly in protected areas in the Iberian Peninsula. Biodiversity metrics and trait patterns allow to understand assemblage's response to habitat and microhabitat characteristics. The presence of rare or redundant species strongly influences the way species loss affects communities. Both taxonomic diversity and functional diversity are necessary for conservation strategies by helping in predicting the vulnerability of saproxylic assemblages to changes or disturbances.